Description of a new species of Nososticta Hagen (Odonata: Platycnemididae: Disparoneurinae) from Central Nicobar Islands, India - Rajeshkumar, S.; Raghunathan, C. (Zootaxa, 2018)
A new damselfly species, Nososticta nancowra Rajeshkumar sp. nov. is described based on eight males and three females from Central Nicobar Islands, India. The diagnostic characteristics of the new species separating it from congeners are discussed. Morphological variations observed in the anal appendages of males and the pronotum of females are documented. A description of the new species using photographs and drawings is given. An identification key to species of the genus Nososticta occurring in Nicobar Islands is given for both sexes.